2017
DOI: 10.1109/tvt.2016.2585381
|View full text |Cite
|
Sign up to set email alerts
|

Decoding-Delay-Controlled Completion Time Reduction in Instantly Decodable Network Coding

Abstract: For several years, the completion time and the decoding delay problems in Instantly Decodable Network Coding (IDNC) were considered separately and were thought to completely act against each other. Recently, some works aimed to balance the effects of these two important IDNC metrics but none of them studied a further optimization of one by controlling the other. In this paper, we study the effect of controlling the decoding delay to reduce the completion time below its currently best known solution in persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Simulations showed that this approach largely outperforms the classical approach using the SSP formulation. The same group of authors extended the study in [152] to the case of lossy intermittent feedback over PECs. Whereas previous works using PECs considered zero error probability (good state always correct and bad state always in error), reference [152] used a non-zero error GEC.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
See 3 more Smart Citations
“…Simulations showed that this approach largely outperforms the classical approach using the SSP formulation. The same group of authors extended the study in [152] to the case of lossy intermittent feedback over PECs. Whereas previous works using PECs considered zero error probability (good state always correct and bad state always in error), reference [152] used a non-zero error GEC.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
“…The same group of authors extended the study in [152] to the case of lossy intermittent feedback over PECs. Whereas previous works using PECs considered zero error probability (good state always correct and bad state always in error), reference [152] used a non-zero error GEC. In contrast with zero error probability in which if an erasure occurs (or do not occur), the sender can surely determine that the channel is in bad state (or good state), in the non zero error GEC this information is never sure and should always be estimated.…”
Section: Trade-off Of Completion Time and Decoding Delaymentioning
confidence: 99%
See 2 more Smart Citations
“…The expressions of these packet combinations can be found in [37] for the completion time and the maximum decoding delay reduction, and in [25] for the sum decoding delay minimization.…”
Section: Imperfect Feedback Scenariomentioning
confidence: 99%